System Implementation and Governance in Sharia Financial Institutions - Samsidar, Samsidar; Arviana, Pipi; Bulutoding, Lince; Muhlis, Syaiful (Invoice : Jurnal Ilmu Akuntansi, 2025)
Islamic finance institutions (IFIs) are bound by principles that extend beyond profit-making; they must ensure accountability to Allah SWT in their operations. These institutions are required to adhere strictly to Sharia standards, which guide their governance and systems. This study aims to examine the implementation of systems and governance in IFIs in Indonesia. A descriptive qualitative approach, utilizing library research, was employed to explore this subject. The findings reveal that the primary goal of the Islamic financial system is to redistribute wealth, facilitating the transfer of funds from savers to borrowers in need, thereby promoting economic growth and enhancing social welfare. Shariah governance (SG) is a unique framework that ensures compliance with Islamic laws, akin to the historical concept of hisbah. Effective governance is essential for the success of Islamic finance institutions, ensuring that they operate in accordance with Sharia principles. This study underscores the significance of SG in regulating these institutions, highlighting the role of the Sharia Supervisory Board (SSB) in maintaining Sharia compliance. Furthermore, regulatory frameworks in Indonesia, including laws and guidelines from the National Shariah Board (DSN), ensure that IFIs adhere to these standards, thereby reinforcing their commitment to Islamic ethics and promoting trust within the community